Analisis Lingkungan Pengendapan Batubara Terhadap Kandungan Total Sulfur Batubara Di Pt Baturona Adimulya, Kabupaten Musi Banyuasin, Sumatra Selatan - Ismi Nur Azizah; Hari Wiki Utama; Jarot Wiratama (Lembaran publikasi minyak dan gas bumi, 2026)
PT Baturona Adimulya operates an open pit mining system. Field conditions indicate variations in coal quality that influence the overall quality of the coal. This study aims to analyze the relationship between the coal depositional environment and the distribution of total sulfur content, as well as to assess the effect of calorific value on moisture content, ash content, and total sulfur. The study uses petrographic (maceral), ultimate and proximate analysis, as well as interpretation based on the Tissue Preservation Index (TPI) and Gelification Index (GI) methods. The results show that seams S and T are dominated by vitrinite macerals consisting of Telocolinite (Tc)